Self-capacity building of small-scale buffalo farmers in pemalang regency Indonesia - Muatip, Krismiwati; Safitri, Lis; Cahyo, Danang Nur (Acta Scientiarum. Animal Sciences, 2024)
This study aims to determine a model for improving the self-capacity of small-scale buffalo farmers in Pemalang Regency, Indonesia. Primary data was collected from buffalo farmers in Pemalang Regency through a survey. Sub-districts were randomly selected as many as 4 out of 14 sub-districts. Two villages were selected for each sub-district. Each selected village was taken as a census respondent. A total of 226 respondents were obtained. The analysis used in this research is descriptive and Structural Equational Modeling - Partial Least Square (SEM PLS) analysis. The study results show buffalo farmers in Pemalang Regency have low to moderate self-capacity so that the number of livestock owned is relatively fixed yearly to raise livestock as savings and social status. Farmers’ self-capacity must be improved by training and counselling through farmer groups. Access to capital and access to information affects farmers’ skills in marketing, provision of feed, and handling of livestock reproduction.